Thallium in terrestrial environments--occurrence and effects - Heim, Martina; Wappelhorst, Olaf; Markert, Bernd (Ecotoxicology, 2002)
In this investigation thallium contents in soil and plants in the EuroRegion Neisse were analysed and the distribution determined. The median top-soil content is 0.5 mg/kg in the area investigated. In this low-contaminated area the moss Pleurozium schreberi contains 0.04-0.13 microg/g and the moss Polytrichumformosum between 0.01 and 0.05 microg/g Tl. The effects of thallium on man and the terrestrial environment were examined. In an epidemiological study a significant positive correlation was found between the thallium content of the two mosses and the incidence of diseases of the circulatory system. The LOEC for thallium in bioassays with terrestrial invertebrates and plants in artificial soil ranged from 1 to 500 mg/kg, which indicates an toxicity of thallium up to 100 times higher than that of Cadmium.
Keywords: Animals; Germany; Soil Pollutants; Oligochaeta; monitorování životního prostředí; Epidemiological Monitoring; mechy; Thallium; látky znečišťující půdu; lidé; Německo; Humans; Incidence; epidemiologické monitorování; incidence; Cardiovascular Diseases; Czech Republic; thallium; Environmental Monitoring; Lepidium; Bryopsida; kardiovaskulární nemoci; Česká republika; Snails; zvířata; Poland; hlemýždi; Polsko